Where do we diagnose HIV infection? Monitoring new diagnoses made in nontraditional settings in England, Wales and Northern Ireland. Issue 7 (9th May 2018) - Croxford, S; Yin, Z; Kall, M; Burns, F; Simmons, R; Copas, A; Ireland, G; Kirwan, P; Chau, C; Delpech, V
Abstract : Objectives: The objectives of the study were to describe 10‐year trends in HIV diagnosis setting and to explore predictors of being diagnosed outside a sexual health clinic (SHC). Methods: Analyses of national HIV surveillance data were restricted to adults (aged ≥ 15 years) diagnosed in 2005–2014 in England, Wales and Northern Ireland. Logistic regression identified factors associated with diagnosis outside an SHC (2011–2014). Results: Between 2005 and 2014, 63 599 adults were newly diagnosed with HIV infection; 83% had a diagnosis setting reported. Most people were diagnosed in SHCs (69%) followed by: medical admissions/accident and emergency (A&E; 8.6%), general practice (6.4%), antenatal services (5.5%), out‐patient services (3.6%), infectious disease units (2.7%) and other settings (4.0%). The proportion of people diagnosed outside SHCs increased from 2005 to 2014, overall (from 27% to 32%, respectively) and among men who have sex with men (MSM) (from 14% to 21%) and black African men (from 25% to 37%) and women (from 39% to 52%) (all trend P < 0.001). Median CD4 increased across all settings, but was highest in SHCs (384 cells/μL) and lowest in medical admissions/A&E (94 cells/μL). Predictors of being diagnosed outside SHCs included: acquiring HIV through heterosexual contact [adjusted odds ratio (aOR) 1.99; 95% confidence interval (CI) 1.81–2.18] or injecting drug use (aOR: 3.28; 95% CI: 2.56–4.19; reference: MSM), being diagnosed late (< 350 cells/μL) (aOR: 2.55; 95% CI: 2.36–2.74; reference: diagnosed promptly) and being of older age at diagnosis (35–49 years: aOR: 1.60; 95% CI: 1.39–1.83; ≥ 50 years: aOR: 2.48; 95% CI: 2.13–2.88; reference: 15–24 years). Conclusions: The proportion of HIV diagnoses made outside SHCs has increased over the past decade in line with evolving HIV testing guidelines. However, the rate of late diagnosis remains high, indicating that further expansion of testing is necessary, as many people may have had missed opportunities for earlier diagnosis.